Echoes of Identity: A Linguistic Odyssey through Sri Lanka’s English Dialects - Ramanayaka, S.K.L.J. (University of Jaffna, 2025)
Language, much like a flowing river, carves its path through the landscapes of human interaction, constantly evolving through regional and cultural influences. This study embarks on an intellectual expedition to unveil the intricate variations of Sri Lankan English across different regions, analyzing their impact on linguistic expression. The research investigates whether geographical influences shape English usage in Sri Lanka and explores the extent to which spoken and written forms diverge across diverse localities. By delving into these linguistic currents, the study aims to illuminate the forces shaping Sri Lankan English as a dynamic second language. A meticulously structured methodology serves as the backbone of this research, ensuring a comprehensive and data-driven analysis of regional linguistic variations. The study encompasses a diverse pool of 150 Craft-level students from nine regional hotel schools under the Sri Lanka Institute of Tourism & Hotel Management (SLITHM). These participants, drawn from distinct linguistic environments, offer a broad spectrum of English usage. Data collection employed a twofold approach: structured questionnaires assessed the nuances of formal written English, while in-depth interviews provided insight into oral communication styles. The gathered data underwent meticulous linguistic scrutiny, dissecting phonetic, syntactic, and lexical variations to reveal the extent of deviation from standard Sri Lankan English. The research uncovers a nuanced linguistic tapestry woven with subtle yet distinct regional variations. While minor phonological and syntactic deviations emerge across Sri Lankan English speakers from different regions, the study finds no substantial evidence of fully distinct dialects. Instead, sociolinguistic factors—such as mother tongue influence, educational background, and regional linguistic exposure—shape the observed linguistic differences. The findings suggest a convergence rather than fragmentation of Sri Lankan English, highlighting a shared linguistic identity that accommodates regional accents and expressions without diverging into wholly separate dialects. Every linguistic inquiry operates within certain boundaries, and this study is no exception. The research primarily focuses on formal spoken and written English, potentially overlooking informal, colloquial, or digital variations that may provide additional insights into regional dialectal influences. Furthermore, while the sample population is diverse, it does not encompass the full breadth of Sri Lanka’s linguistic landscape, leaving room for future research to expand the scope. Subsequent studies could incorporate a wider demographic range, including professionals from different sectors, to deepen the understanding of regional English usage. These future explorations could further enrich Sri Lanka’s linguistic discourse and aid in shaping educational and policy frameworks for English language instruction. This research contributes significantly to the field of sociolinguistics by mapping the subtle dialectal nuances of Sri Lankan English, reinforcing its evolving identity in the global linguistic landscape. By charting these variations, the study underscores the importance of fostering a unified Sri Lankan English identity that acknowledges regional influences while promoting linguistic cohesion. In a world where English continues to adapt and transform, understanding these dialectal intricacies is essential for educators, linguists, and policymakers striving to establish a balanced and inclusive linguistic standard. Ultimately, this study not only captures the echoes of regional identity within Sri Lankan English but also paves the way for future linguistic explorations, ensuring that language remains a bridge rather than a barrier in Sri Lanka’s rich and diverse communicative fabric.
Keywords: Dialectal variations; Linguistic identity; Phonological differences; Regional Influences; Sociolinguistics